PENINGKATAN UNJUK KERJA TURBIN ANGIN ROTOR SAVONIUS DENGAN PEMAKAIAN ABAR SENTRIFUGAL, HOOD DAN RUDER - Purwanto, Adi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
Clean water performing for urban society is a serious problem, because clean water is very important thing not only for life but also for home industry. To supply clean water from water sources to urban society neighborhood is needed a very expensive equipment, including the operational cost. Wind turbine is right solution to solve this problem as a energy source for water supplying for urban society because wind energy is available along a years. Savonius Rotor Wind Turbine is one of many Turbine Wind types. Savonius Rotor is a vertical shaft rotor type which simple construction and low cost production. Increasing the performance of this rotor is earned by using design optimization and modification method. This a low speed turbine need wind energy speed of 3–4 Beaufort Scale (7-16 knot) which has Centrifugal Brake, Hood and Ruder. This Savonius Rotor can supply 284, 47 Watt of electrical power that is used to water pumping.